>
数学
>
先化简,再求值:(3x+1)(2x-3)-(6x-5)(x-4),其中x=-2.
人气:338 ℃ 时间:2020-02-02 23:36:42
解答
原式=6x
2
-9x+2x-3-(6x
2
-24x-5x+20)=6x
2
-9x+2x-3-6x
2
+24x+5x-20=22x-23,
当x=-2时,原式=-44-23=-67.
推荐
先化简,再求值:(3x+1)(2x-3)-(6x-5)(x-4),其中x=-2.
先分解因式,再求值.(2x+1)2(3x-2)-(2x+1)(3x-2)2-x(2x+1)(2-3x),其中x=3/2.
先化简,再求值:(3x-1)(2x+3)-(x-2(6x-5),其中x=-3/8
化简求值(3x+1)(2x-3)-(6x-5)(x-4),其中x=-2分之1
化简再求值:6X^2-(2X-1)(3X-2)+(X+2)(X-2),其中X=2
两数和为3,积为-10 求这两个数
用英语简单描写你的房间
以我的卧室写一篇英语作文
猜你喜欢
carefully
After paying 1000 dollars ____,you will all become full memebers of our club A each B all c every
Our class has a map of the world (改为同义句)
The baby didn't cry any more when she saw her mother.同义句
How do you go to school,on foot or by bus?
时间旅行的悖论
设f(x)=ax7+bx5+cx3+dx+5,其中a,b,c,d为常数.若f(-7)=-7,则f(7)=_.
计算1-3+5-7+9-11+…+97-99.
© 2024 79432.Com All Rights Reserved.
电脑版
|
手机版